The prognostic value of a prominent Q wave in lead (-)aVR in acute anterior wall myocardial infarction - Leili Pourafkari; Nader D Nader; Navid Heydari; Arezou Tajlil; Samad Ghaffari (KARE Publishing, 2015)
OBJECTIVE: This study aimed to determine the association of a prominent Q wave in lead (-)aVR with clinical, echocardiographic and angiographic findings in anterior ST elevation myocardial infarction (STEMI) and to evaluate the role of this finding in short-term and long-term outcomes. METHODS: During a one-year period, 150 patients with first time anterior STEMI were screened and 121 patients with no other cardiopulmonary and renal comorbid diagnoses were included in the study. Patients were allocated into two groups based on presence or absence of a prominent Q wave in lead (-)aVR. All clinical, electrocardiographic, echocardiographic and angiographic data were recorded and compared between the groups. In-hospital adverse outcomes and mortality as well as two-year survival were also compared. RESULTS: Among 121 patients (mean age: 62.8+-12.5 years) 26.4% had a prominent Q wave in lead (-)aVR. The prevalence of multi-vessel disease was higher in patients with a Q wave (76.9% vs. 52.8%, p=0.03). ST-segment elevation in lead V6 was significantly more common in those with a Q wave (50% vs. 30.3%, p=0.04). Posterobasal region motion abnormality was more common in the Q wave group. (9.4% vs. 1.2% respectively, p=0.04). Overall, mortality was higher in the Q wave group; however, it was not statistically significant (15.4% vs. 9.3%, p=0.39). CONCLUSION: In anterior STEMI, presence of a Q wave in lead (-)aVR is associated with occlusion of multiple arteries. Shortand mid-term mortality are not affected by this ECG finding.